Analisis Kendala Dan Alternatif Pembelajaran Fisika Di SMP Negeri 2 Padangsidimpuan - Melisa Anjelita Hutabarat; Eni Sumanti Nasution (Universitas Gara Nusantara Padangsidimpuan, 2024)
In distance learning, this is a new thing for physics learning methods in schools, especially being a challenge for educators. Online and face-to-face learning takes turns creating a new atmosphere in the learning process. There were many obstacles during its implementation. The school also provides several alternatives in dealing with obstacles experienced in the learning process during the COVID-19 pandemic. This research is entitled Analysis of Constraints and Alternatives to Physics Learning During the Covid-19 Pandemic Period at SMP Negeri 2 Padangsidimpuan with the aim of knowing the obstacles experienced and the alternatives provided in helping the learning process of physics at SMP Negeri 2 Padangsidimpuan. The approach that the author uses in this research is a qualitative descriptive approach, this is obtained from an incident that occurs in the surrounding environment so as to produce the necessary information. From the results of the analysis, it was concluded that the obstacles experienced by teachers, both online and face-to-face learning, were the difficulty of knowing the level of understanding of each student, determining the right learning model during the COVID-19 pandemic, and lack of understanding in the use of technology. Students find it difficult to learn independently and do not understand the material given because it is only limited to theory. Schools find it difficult to determine appropriate actions for the learning process, and provide distance learning facilities on a regular basis. In dealing with these obstacles, several alternatives are given, namely, schools provide permission to conduct online learning activities, provide facilities in the form of internet quotas, send pdf and video books related to physics subject matter and conduct discussions among teachers in introducing technology. At face-to-face meetings, the school determines the learning schedule by taking turns, following the health protocol.